Factors demotivate the adaptability of organic farming among small scale pineapple farmers in Batu Pahat, Johor / Mohd Nazri Mohd Nasir - Mohd Nasir, Mohd Nazri (Faculty of Plantation and Agrotechnology, 2015)
Organic farming is the way to achieve the healthy food in order to improve living standard nowadays. With more people are aware of the cleanliness and healthiness of their food, farmers must adapt to fulfill the customer demand by changing their conventional farming to organic farming. In Malaysia, pineapple is a popular commercial fruit, that sometimes people eat them freshly. Statistically, the world organic production is uncertain and not constant. There are two main problems or issue regarding this study. Firstly is the effect on our environment and daily life from the excessive usage of chemical pesticides. Secondly is the issue of the increasing awareness regarding healthy lifestyle, which is to consume healthy food such as organic food. Country such as Singapore had once rejected our agriculture product due to high content of Maximum Residues Level (MRL). So, the purpose of this study is to study the reason why pineapple farmers are not applying organic farming. This study to be conducted to reach the objective of relationship between the independent variables (organic farming knowledge and environmental awareness) and the dependent variables which is the pineapple farmer's adoptability to organic farming. The methodology of this study is by questionnaires, which the question was obtained from suitable previous study by other researches. The information will be gained by distributing set of questionnaires to the pineapple farmers in Batu Pahat, Johor. The statistical analysis test that will be use is, descriptive statistic test, Pearson correlation and multiple regressions. The result of this study shows that there is no significant relationship between both of the knowledge of organic farming and environmental awareness and the farmer's adaptability of organic farming.